INTRAOPERATIVE RISK FACTORS OF MYOCARDIAL INFARCTION IN NON-CARDIAC SURGERIES - Z. Т. Kotvitskаya; G. B. Kolotovа; V. А. Rudnov; V. A. Bаgin (Вестник анестезиологии и реаниматологии)
The objective of the study: to find peri-operative risk factors of myocardial infarction during the intra-operative period in the patients undergoing non-cardiac surgery.Subjects and methods. 85 case histories of patients were analyzed, all those patients developed myocardial infarction after surgeries (non-cardiac) in the post-operative period. Clinical and electrocardiogram parameters, outcomes of peri-operative myocardial infarction and its intra-operative risk factors were analyzed. The comparison group included 80 patients who had surgeries with the favorable course of the post-operative period.Results: 72.9% of cases developed myocardial infection in the post-operative period with the 1st day after surgery and had blurring clinical signs of it: it was not accompanied by pain syndrome in 23.5% of cases, and there was no ST elevation on ECG in 69.4% of cases. Risk factors of myocardial infection in the post-operative period were the following: duration of surgery for more than 90 minutes, intra-operative hypotension (systolic arterial pressure < 100 mm Hg.) for more than 10 minutes, anemia with hemoglobin level less than 70 g/l, cardiac rhythm in the peri-operative period more than 90 bpm. Results of the logistic multi-factorial analysis showed that reduction of systolic arterial pressure less than 100 mm Hg., OR 4.24 (1.181–15.20), p = 0.026, was the only independent risk factor of myocardial infarction.